Fish eDNA detections in ports mirror fishing fleet activities and highlight the spread of non-indigenous species in the Mediterranean Sea. (April 2023) - Aglieri, Giorgio; Quattrocchi, Federico; Mariani, Stefano; Baillie, Charles; Spatafora, Davide; Di Franco, Antonio; Turco, Gabriele; Tolone, Marco; Di Gerlando, Rosalia; Milazzo, Marco
Abstract: Gathering comprehensive marine biodiversity data can be difficult, costly and time consuming, preventing adequate knowledge of diversity patterns in many areas worldwide. We propose fishing ports as "natural" sinks of biodiversity information collected by fishing vessels probing disparate habitats, depths, and environments. By combining rapid environmental DNA metabarcoding (eDNA) surveys and data from public registers and Automatic Identification Systems, we show significant positive relationships between fishing fleet activities (i.e. fishing effort and characteristics of the fishing grounds) and the taxonomic fish assemblage composition in eleven Mediterranean fishing ports. Overall, we identified 160 fish and 123 invertebrate OTUs, including at least seven non-indigenous species, in some instances well beyond their known distribution areas. Our findings suggest that eDNA assessments of fishing harbours' waters might offer a rapid way to monitor marine biodiversity in unknown or under-sampled areas, as well as to reconstruct fishing catches, often underreported in several regions. Highlights: Ports work as sinks of biodiversity information collected by fishing vessels. eDNA fish diversity estimates are correlated to fishing effort. New large-scale fish diversity and fishery catch assessments protocols Spatio-temporal monitoring of alien species invasion fronts